The role of Islamic Sukuk in Absorption of Deficit Budget : Indonesia and Malaysia cases - Mehdaoui, Hind; Bouchaib , Belhadj (Journal of Human Sciences, 2022)
The aim of this study is to identify the islamic sukuk and its development in recent last years, and its role in absorption budget deficit, this instruments are used in strengthen the infrastructure also they have an effectiveness contribution to reduce the budget deficit. Indonesia and Malaysia are considered among the pioneering countries in using sukuk to absorb the public budget deficit, as it has become one of the monetary policy tools to control the amount of cash circulating in society.